ENT 600: U Mobile Setia City Mall / Nur Amirah Roslan … [et al.] - Roslan, Nur Amirah; Mohd Arif, Izyan Khalidah; Abd Malek, Nur Nadhira; Roslan, Najwa Nadeera (2019)
In this company analysis, we selected U Mobile Setia City Mall as our case to be studied. This study is conducted to analyse the problems faced by U Mobile Setia City Mall. Moreover, this case study provides some solution that can help the company to improve their business and indirectly can solve their problems and increases their sales. In the first part of the study, we conducted an interview with one of the employees that works in U Mobile Setia City Mall. The information obtained include the background of the company, organizational structure, products and services provided, technology applied as well as their financial status. Next, we also gather the information on how they market their business and its operational strategy that the company used to promote their products and services. In their financial achievement, we are able to know their achievements gain from the financial management. Every company has sets their own strategy in achieving the goals. Therefore, SWOT analysis is done by analysing the company's strength, weakness, opportunities and threats in real business world. By doing this, we get to analyse and find solution in order to fulfil and overcome the Consumer Trend Canvas (CTC) analysis. Thus, customers' needs and expectations can be achieved. The problems faced by U Mobile Setia City are classified under finding and discussion where the problems and how it is being solved are being analysed and discussed. The recommendations and improvements will help U Mobile in solving their problems.